Liability of Notary/Official Certifier of Title Deeds as Perpetrators of Falsification of Letters and Legal Consequences on The Object of Dependent Rights Guaranteed by Unauthorized Parties (Case Study of Family Land Dispute Nirina Zubir) - Winnie Nathalia Wenur; Mohamad Fajri Mekka Putra (LEGAL BRIEF, 2022)
The case that happened to the family of artist Nirina Zubir is no longer foreign because it has been spread in various mass media in Indonesia. This case is where the problem boils down to the transfer of land rights carried out without rights by an unauthorised party, namely the household assistant of Nirina Zubir's own family. In this case, the involvement of a Notary and Land Deed Officials is actually the key to the success of the transfer of land rights without these rights. This is because the household assistant of Nirina Zubir's family changed the name of the certificate belonging to Nirina Zubir's mother and then carried out various legal actions on it with the help of a Notary and Land Deed Making Officer in their respective positions. The existence of Notaries and Land Deed Making Officials should help create legal certainty for land rights owned by the Indonesian people. However, in this case, the public officials are also the perpetrators of the crime. Not only involving the Notary, Land Deed Officials, and Nirina Zubir's family, but furthermore, this case also involved banking institutions. This is because several certificates belonging to the family of Nirina Zubir, which have been illegally renamed, are then used as collateral for the credit of the household assistant of Nirina Zubir's family, as a party who has no right to carry out such legal actions. Because of the many parties involved, this case becomes very interesting to study from various sides, especially in terms of the accountability of the Notary and Land Deed Making Officials involved, as well as on legal certainty over the existing mortgage object.